Ethnomathematics: Conceps of Mathematics in The Context Of "Siwaluh Jabu" Karo Traditional House - Dewi, Siti Kumala; Asrul, Asrul (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
One of the Karo traditional cultures that incorporates elements of ethnomathematics in its shape is the "Siwaluh Jabu" roof design. In order to apply the mathematical ideas discovered as a method for teaching mathematics in schools, the study's objective was to investigate the mathematical ideas present in the "Siwaluh Jabu" roof design. Through observation, interviews, documentation, and an ethnographic approach, this study also used a literature review and a descriptive qualitative methodology. The Miles and Huberman method, which entails data reduction, data presentation, and conclusion drawing, is used in the data analysis process. The study's findings revealed the concepts of a flat shape, spatial geometry, and congruence. The results of this study can be used as learning aids and approaches to learning mathematics.